Potential biotechnological application of microalgae: a critical review. (2nd January 2017) - Odjadjare, Ejovwokoghene C.; Mutanda, Taurai; Olaniran, Ademola O.
Abstract: Microalgae are diverse microorganisms inhabiting a wide range of habitats with only a small fraction being cultivated for human use. Recently, interest in microalgal research has increased in the quest for alternative renewable fuels due to possible depletion of fossil fuels in the near future. However, costly downstream processing has hampered the commercialization of biofuels derived from microalgae. Several value added products of industrial, pharmaceutical and agricultural relevance could be simultaneously derived from microalgae during bioenergy production. Despite these value-added products having the potential to offset the high cost of downstream processing of renewable fuels, their production has not been explored in-depth. This review presents a critical overview of the current state of biotechnological applications of microalgae for human benefit and highlights possible areas for further research and development.